2021
DOI: 10.1016/j.fastrc.2021.100006
|View full text |Cite
|
Sign up to set email alerts
|

Surgical treatment of a navicular osteochondral lesion using microionized cartilage matrix: A case report

Abstract: Osteochondral lesions of the tarsal navicular are uncommon but can lead to long-term complications if misdiagnosed or left untreated. Recent literature suggests successful outcomes with the use of microionized cartilage matrix allograft for the treatment of osteochondral lesions in the ankle. In this report we will present a unique case of navicular osteochondral lesion in a collegiate-level dancer which the patient suffered during a competition. The patient ultimately went on to have surgical intervention inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 26 publications
(46 reference statements)
0
3
0
Order By: Relevance
“…[8][9][10] These treatments can improve some of the symptoms, but some adverse reactions are reported. 11,12 In recent years, tissue engineering (TE) has made considerable progress in obtaining functional articular cartilage. However, currently popular tissue engineering methods are difficult to restore damaged sites to their normal state because of their limited ability to rebuild anisotropic structures in native cartilage tissue.…”
Section: Introductionmentioning
confidence: 99%
“…[8][9][10] These treatments can improve some of the symptoms, but some adverse reactions are reported. 11,12 In recent years, tissue engineering (TE) has made considerable progress in obtaining functional articular cartilage. However, currently popular tissue engineering methods are difficult to restore damaged sites to their normal state because of their limited ability to rebuild anisotropic structures in native cartilage tissue.…”
Section: Introductionmentioning
confidence: 99%
“…Like OCLs of the talus, navicular OCLs can be managed nonoperatively with arch supports, immobilization, limited weightbearing, nonsteroidal antiinflammatory drugs, activity modifications, and physical therapy. 1 , 3 Described operative interventions for navicular OCLs include transplantation of iliac crest bone graft, 3 micronized cartilage matrix, 6 osteochondral autograft transplantation (OATS), 5 and flowable collagen with iliac crest bone marrow aspirate concentrate (BMAC) and fibrin glue. 4 In this report, we present 2 cases of navicular OCLs: one primary lesion treated with autologous bone grafting and cartilage resurfacing with lyophilized collagen II (BioCartilage; Arthrex, Naples, FL) and BMAC, and a second revision lesion after failed microfracture treated with OATS.…”
Section: Introductionmentioning
confidence: 99%
“…The stress fracture was corrected using a cannulated screw. Recently, Togher et al 11 reported that OCL of the tarsal navicular was treated with microionized cartilage matrix allograft and revealed the excellent post-operative outcome.…”
Section: Introductionmentioning
confidence: 99%